Strategi Pencegahan dan Pengendalian Faktor Risiko Penyakit Kardiovaskular melalui Peningkatan Pengetahuan dan Pengukuran Kesehatan - Wahyuni Arumsari; Dwi Nur Siti Marchamah; Feiza Jaya Dilaga; Rita Amelia Putri (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Cardiovascular disease is still a health problem at this time. This can increase the morbidity, disability, and socio-economic burden on society. The main indicator for cardiovascular disease is the quality of life of a person. Therefore, early detection of the risk of cardiovascular disease is needed so that it can be studied further, monitored, and given appropriate interventions by health workers. This community service activity was divided into 3 sessions including carrying out the pretest, KIE and posttest, and health measurements in the form of measuring blood pressure and cholesterol levels. In the IEC session, the material that will be delivered is the introduction and control of risk factors for heart disease (hypertension and high cholesterol levels); balanced nutritional intake for people with hypertension and high cholesterol; hypertension as co-morbid co-19; the benefits of physical activity for people with hypertension and high cholesterol; and health measurement in the form of measurement of blood pressure and cholesterol.